2019
DOI: 10.1109/tpel.2018.2880935
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Validation of Harmonic Impedance Measurement and LTP Nyquist Criterion for Stability Analysis in Power Converter Networks

Abstract: This paper presents the first experimental validation of the stability analysis based on the online measurement of harmonic impedances exploiting the Linear Time Periodic (LTP) approach, applied to AC networks of power converters. Previous publications have provided the theoretical framework for the method, enabling the stability assessment of an unknown system adopting a blackbox approach, relying only on injected perturbations and local measurements. The experimental case study considered in this paper compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…However, the inductance values in these studies are unrealistically high with regard to public LV networks (e.g., 12.8 mH [34]). Furthermore, existing black-box studies only indicate that the inverters will eventually become instable [38], but provide no experimental proof of the minimal required phase margin in practical applications. In contrast, this study accurately calculates the specific critical conditions for a commercially available PV inverter and validates the preciseness of the fully measurementbased black-box stability assessment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the inductance values in these studies are unrealistically high with regard to public LV networks (e.g., 12.8 mH [34]). Furthermore, existing black-box studies only indicate that the inverters will eventually become instable [38], but provide no experimental proof of the minimal required phase margin in practical applications. In contrast, this study accurately calculates the specific critical conditions for a commercially available PV inverter and validates the preciseness of the fully measurementbased black-box stability assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing Case II and Case III, it is indicated that the converter control on the harmonic mitigation can result in a reduced-order modeling of the converter-based system. That is to say, truncation relying only on the system's steady-state harmonics like in [9]- [12] may result in a more conservative truncation order.…”
Section: Case Iii: Unbalanced Grid Condition With Advanced Pllmentioning
confidence: 99%
“…HTFs are thus more feasible than the HSS models, since they can directly characterize the system's dynamics from the input-output perspectives, even without knowing the internal control details. Moreover, the HTFs can be obtained easily by the frequency-scan measurement [8], [9] and further used for stability analysis based on the Nyquist stability criterion [9]- [12].…”
Section: Introductionmentioning
confidence: 99%
“…Since the admittance model is truncated by a 6-by-6 matrix, the frequency scan measurement should inject perturbations 6 times to measure all the elements of ( 27) [46]. The frequency is scanned within the fundamental frequency interval of the HTF model, i.e., (0, 100) Hz.…”
Section: Grid Simulator Inverter 2 As Current Perturbation Sourcementioning
confidence: 99%